1987
DOI: 10.1002/em.2860090106
|View full text |Cite
|
Sign up to set email alerts
|

Methyl isocyanate: An evaluation of in vivo cytogenetic activity

Abstract: The ability of inhaled methyl isocyanate (MIC) to induce genotoxic and cytotoxic damage in vivo was evaluated by assessing the induction of chromosomal aberrations (CAs) and sister chromatid exchanges (SCEs) in bone marrow metaphase cells, the induction of micronuclei in polychromatic erythrocytes (MN-PCEs), and the inhibition of bone marrow cellular proliferation and erythropoiesis. B6C3F1 mice were exposed to MIC by two exposure regiments: in two experiments, male mice only were exposed to 3, 10, and 30 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…Depression of mitotic (MI) and replicative indices (RI) in Ghosh et al [26] study was not consistent with MIC-exposure in Bhopal population, which was consistent with Conner et al [32] in murine alveolar macrophages. However, delayed cell cycle was reported by Deo et al [28] in peripheral lymphocytes of the MIC-exposed people, and also in experimental animals [33].…”
Section: Chromosome Aberrations (Ca)mentioning
confidence: 83%
See 1 more Smart Citation
“…Depression of mitotic (MI) and replicative indices (RI) in Ghosh et al [26] study was not consistent with MIC-exposure in Bhopal population, which was consistent with Conner et al [32] in murine alveolar macrophages. However, delayed cell cycle was reported by Deo et al [28] in peripheral lymphocytes of the MIC-exposed people, and also in experimental animals [33].…”
Section: Chromosome Aberrations (Ca)mentioning
confidence: 83%
“…However, a significant increase in micronucleated polychromatic erythrocytes was observed in peripheral blood of male mice in one experiment. Genotoxic/ cytotoxic effect was evidenced through depression in bone marrowcellularity in animals exposed by inhalation [33]. Genotoxic response of MIC-modified DNA described decrease in plaque formation in E. coli.…”
Section: Chromosome Aberrations (Ca)mentioning
confidence: 99%
“…Besides, the immunotoxic (Karol et al, 1987), genotoxic (Conner et al, 1987;Tice et al, 1987), reproductive and developmental toxic effects (Schwetz et al, 1987) are well-documented in humans and animals. However, the etiology of MIC in carcinogenesis is far from completely understood (Senthilkumar et al, 2012;Senthilkumar, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Striking findings of resistance were documented in plants like Artocarpus integrifolia, Casuarina equisetifolia, Ficus bengalensis and Mangifera indica [8] Genotoxic potential of MIC in exposed animal subjects MIC has a significant potential for inducing cancer in rodents [47] Sister chromatid exchanges (SCEs) and cell cycle kinetics in murine tissues [40] Chromosomal aberrations and sister chromatid exchanges in bone marrow metaphase cells, induction of micronuclei in polychromatic erythrocytes and the inhibition of bone marrow cellular proliferation and erythropoiesis in mice [48] In vivo micronucleus test, chromosomal aberrations, sister chromatid exchanges in bone marrow cells of rodent somatic cells [49] In vivo micronucleus test and chromosomal analysis of bone marrow cells in mice [50] Mutagenic and cytotoxic effects in mouse micronucleus test [51] Genotoxic potential of MIC in exposed human subjects…”
Section: Methyl Isocyanate and Cytogenetic Damagementioning
confidence: 99%
“…The non-targeted effects of toxic exposure such as bystander responses, genomic instability, gene induction, adaptive responses and low hypersensitivity may also be mirrored as trans-generational health effects. Sarangi et al [57] report that exposure of pregnant workers have demonstrated that exposure to MIC by inhalation results in bone marrow damage, indicating that MIC or its reactive metabolites possess systemic genotoxic/cytotoxic activity [48][49][50]. MIC exposure was found to lead to inhibition of bone marrow cell proliferation by evaluation of the mutagenic and cytotoxic effects of MIC with a mouse micronucleus test [51].…”
Section: Methyl Isocyanate and Cytogenetic Damagementioning
confidence: 99%